TEACHING ENGLISH VOCABULARY THROUGH DRAMA: AN EXAMPLE OF GÖLBAŞI VOCATIONAL SCHOOL - Hakkı ŞİMŞEK (Fırat University, 2019)
Teaching English vocabulary is one of the most challenging areas in language teaching. To communicate in a language in all possible situations one needs a good knowledge of vocabulary; however, it takes quite a long time to be competent in English vocabulary in Turkey’s context since English is learned as a foreign language in our education system. Learners do not have chance to practice the target language outside the classroom thus, they easily forget what is learned due to lack of practice. To overcome these problems various techniques such as flashcards, keywords, games, pictures, drawings etc. are adapted and applied by the instructors in language classrooms; however, unfortunately, the instructors just ended up giving the Turkish equivalent of the words at the end of the class. Namely the vocabulary items fall into disuse. With these problems in mind the aim of this study is to see the effects of using drama in vocabulary teaching on students. The study was carried out with the students of Gölbaşı Vocational School of Adıyaman University. The data was collected through a pre-test and post-test for vocabulary learning scores and an attitude questionnaire were applied to the participants to get their views on the subject. At the end of the study it is found out that the participants were eager to learn vocabulary through drama activities and the analysis of the test scores showed that there is a significant difference between the test scores before and after applying the drama activities. We think that teaching vocabulary through drama will serve for the field as an alternative method in English vocabulary teaching.